Expectation adaptation during natural reading. Issue 10 (1st December 2020) - Yan, Shaorong; Jaeger, T. Florian
ABSTRACT: Implicit expectations play a central role in sentence processing. These expectations are often assumed to be static or change only at relatively slow time scales. Some theoretical proposals, however, hold that comprehenders continuously adapt their expectations based on recent input. Existing evidence has relied heavily on self-paced reading, which requires familiarisation with a novel task. We instead employ eye-tracking reading to investigate the role of expectation adaptation during speeds and task demands more closely resembling natural reading. In two experiments, subjects read sentences that contained higher than expected proportions of a previously highly unexpected structure (reduced relative clauses). We test how this change in the statistics of structures within the experiment affects reading: if subjects adapt their expectations, reading times for the unexpected structure should decrease over the course of the experiment. This prediction is confirmed in both experiments. Significant effects of the changing statistics are observed for regression-related measures but not first-pass reading measures. We discuss possible accounts of this pattern in the eye-movement record.